Overall and progression‐free survival of Afro‐Caribbean men with metastatic castration‐resistant prostate cancer (mCRPC). Issue 2 (25th November 2021) - Vestris, Pierre‐Gilles; Gourtaud, Gilles; Senechal, Cédric; Sadreux, Yvanne; Roux, Virginie; Blanchet, Pascal; Brureau, Laurent
Abstract: Introduction: Several studies in the Caucasian population have shown the benefit of using docetaxel, abiraterone, or enzalutamide for patients with metastatic prostate cancer at the castration‐resistant stage (mCRPC). However, there are no strong data for men of African ancestry. The objective of this study was to estimate the overall and progression‐free survival of patients according to these treatments at the mCRPC stage. Patients and Methods: This was a monocentric retrospective study that consecutively included 211 men with mCRPC between June 1, 2009 and August 31, 2020. The primary end point was overall survival (OS). The secondary end point was progression‐free survival. Kaplan–Meier survival and Cox proportional hazard analyses were performed. Results: The present study included 180 patients for analyses. There was no difference in OS (log‐rank test = 0.73), with a median follow‐up of 20.7 months, regardless of the treatment administered in the first line. Men with mCRPC who received hormonotherapy (abiraterone or enzalutamide) showed better progression‐free survival than those who received docetaxel (log‐rank test = 0.004), with a particular interest for abiraterone hazard ratio (HR) = 0.51 (95% confidence interval: 0.39–0.67). The patient characteristics were similar, except for bone lesions, irrespective of the treatment administered in the first line. After univariate then multivariate analysis, only World Health Organization status and metastases at diagnosis were significantly associated with progression. Conclusion: Our results suggest the use of hormonotherapy (abiraterone or enzalutamide) with a tendency for abiraterone in first line for men with African ancestry at the mCRPC stage.